Influence of reactive and maximum strength indicators on sprint performance - Healy, R.; Smyth, C.; Kenny, C. I.; Harrison, J. A. (The Journal of Strength and Conditioning Research, 2019)
The primary aim of this study was to assess the relationship between reactive and maximal strength measures with 40 m sprint performance and mechanical properties. Fourteen male and 14 female sprinters participated in this study. On the first day, subjects performed 40 m sprints with 10-m split times recorded in addition to maximal theoretical velocity, maximal theoretical force and peak horizontal power, which were calculated from force-velocity relationships. On the second day, subjects performed isometric midthigh pulls (IMTPs) with peak force (PF) and relative PF calculated, drop jumps (DJs) and vertical hopping where the reactive strength index (RSI) was calculated as jump height (JH) divided by contact time (CT). Pearson correlations were used to assess the relationships between measures and independent samples t-tests were used to assess the differences between men and women. No significant correlations were found between DJ and hopping RSI and sprint measures. A significant strong positive correlation was found between IMTP PF and peak horizontal power in men only (r = 0.61). The male sprinters performed significantly better in all recorded measures apart from hopping (CT, JH and RSI) and DJ CT where no significant differences were found. The lack of association between reactive and maximal strength measures with sprint performance is potentially because of the test's prolonged CTs relative to sprinting and the inability to assess the technical application of force. Several methods of assessing reactive strength are needed that can better represent the demands of the distinct phases of sprinting e.g., acceleration, maximum velocity.